2016
DOI: 10.1016/j.juro.2016.01.121
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Renal Function after Percutaneous Nephrolithotomy—Does the Number of Percutaneous Access Tracts Matter?

Abstract: Multi-access percutaneous nephrolithotomy is associated with a small reduction in the function of the targeted kidney compared to a single access approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
2
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 18 publications
6
25
2
3
Order By: Relevance
“…It has been shown that the need for blood transfusion was more common in patients undergoing multi-access PCNL than in those having single-access PCNL (9,10,11,12). On the contrary, there were also studies reporting that multi-access did not increase the need for transfusion (4). In our study, however, the need for blood transfusion was statistically significantly more in the multi-access group than in the single-access group.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…It has been shown that the need for blood transfusion was more common in patients undergoing multi-access PCNL than in those having single-access PCNL (9,10,11,12). On the contrary, there were also studies reporting that multi-access did not increase the need for transfusion (4). In our study, however, the need for blood transfusion was statistically significantly more in the multi-access group than in the single-access group.…”
Section: Discussioncontrasting
confidence: 76%
“…For this reason, single-access is not always sufficient for the treatment of kidney stones and multiaccess is sometimes required for stone removal. The effect of multi-access on renal functions, as well as complications, such as low hemoglobin (Hb) values and postoperative infection, is a controversial issue (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Bu formül ile, kişilerin böbrek fonksiyonları yaşları, vücut ağrılıkları ve serum kreatinin düzeyleri kullanılarak kolay bir şekilde değerlendirilebilir [14]. Fakat, tek bir renal üniteye yönelik girişim yapılan hastalarda, renal fonksiyonların global kreatinin-bazlı değerlendirilmesi, girişim yapılmayan karşı taraftaki böbreğin de katkısıyla kafa karıştırıcı olabilir ve etkilenen böbreğe yönelik olarak yeteri kadar duyarlı olmayabilir [15]. Bu nedenle, nükleer renal sintigrafiler, her bir renal ünitenin fonksiyonlarının değerlendirmesinde daha doğru sonuçlar vermekle birlikte, olası bir obstrüksiyon varlığını da gösterebilmektedirler.…”
Section: Tablo 2 Postoperatif Böbrek Fonksiyon Değişimleri (Ort±ss)unclassified
“…Gorbachinsky ve arkadaşlarının PNL uyguladıkları 307 hasta içerisinden preoperatif ve postoperatif renogramları olan 110 hastanın 1 yıl içerisindeki böbrek fonksiyonlarını değerlendirdikleri retrospektif çalışmalarında, tek giriş yapılan 74 hasta ile çoklu giriş yapılan 36 hastanın serum kreatinin ve MAG3 nükleer renogram bazlı böbrek fonksiyonlarını karşılaştırmışlardır [15]. Serum kreatinin ölçümleri preoperatif 1 ay içerisinde ve erken postoperatif dönemde ölçülürken, nükleer çalışmalar ameliyattan önceki 1 ay içerisinde ve sonrasındaki 4 ay içerisinde yapılmıştır.…”
Section: Tablo 2 Postoperatif Böbrek Fonksiyon Değişimleri (Ort±ss)unclassified
See 1 more Smart Citation